A Review of Post and Core Application with Emphasize on Non Metallic Posts - Shahroodi MH; Berenji H (Tehran University of Medical Sciences, 2001)
Many different methods are suggested to restore endodontically treated teeth. Prefabricated posts can not be indicated for all teeth and cast posts require extra time and cost. In addition, with the introduction of full ceramic restorations, achieving the ideal esthetic with metal post underneath them may be problematic or impossible because the darkness of the metallic posts may show through the highly translucent all ceramic restorations. In this article the review of litature and describiton of applied methods of different procedure in restoring the root canal therapied teeth and few techniques of non metallic posts fabrication such as fiber reinforced composite and zirconium oxide posts have been described.